MANAJEMEN BOARDING SCHOOL DALAM PENINGKATAN PRESTASI DAN KARAKTER RELIGIUS SISWA MA’HAD ALQOLAM MAN 2 KOTA MALANG - Ihsan Zikri Ulfiandi (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2022)
Boarding school management is a school management system that has a dormitory, where students live and study together every day in the scope of the school/madrasah. efficient. In increasing achievement and religious character, students must use careful planning so that the implementation can run according to the goals that have been set. Because the existence of high achieving schools is often identified with good management, complete facilities and infrastructure, structured curriculum, and qualified educators and education personnel according to their fields of expertise. The focus of this research is: 1) how to plan a boarding school program in improving the achievement and religious character of Ma'had Al-Qolam MAN 2 Malang City students, 2) how to implement a boarding school program in improving the achievement and religious character of Ma'had Al-Ma'had students. Qolam MAN 2 Malang City,, 3) how is the evaluation of the boarding school program in improving the achievement and religious character of Ma'had Al-Qolam MAN 2 Malang City students, 4) how are the results of the boarding school program in improving the achievement and religious character of Ma'had Al students -Qolam MAN 2 Malang City, This study uses a qualitative approach, where in this case the researcher understands the phenomena that occur and in maintaining the authenticity of the data, the researchers are actively involved and go to the field directly. Data collection techniques used direct observation, in-depth interviews with several informants and documentation. The data that has been obtained will be processed using a data reduction process, data presentation and conclusion drawing. The credibility of the data is done through checking the triangulation procedure of data sources and techniques. The results showed that: 1) program planning in improving the achievement and religious character of the students of Ma'had Al-Qolam MAN 2 Malang City used four references, namely: a. The basic value of Ma'had, b. madrasa vision and mission, b. strategic plan, c management guidelines; 2) the implementation of the achievement improvement program begins with a. selection of new student admissions, b. Mapping student classes, c. Implementation program, d. coaching pattern; 3) Evaluation includes a. directly and b. indirect. 4) The results of the program are a. achievement of targets and b. Award. Abstrak Manajemen boarding school merupakan sebuah sistem pengelolaan sekolah yang memiliki asrama, di sanalah para siswa tinggal dan belajar bersama setiap harinya di ruang lingkup sekolah/madrasah. Dalam peningkatan prestasi dan karakter religious siswa harus menggunakan perencanaan yang matang sehingga pelaksanaannya dapat berjalan sesuai dengan tujuan yang telah ditetapkan. Fokus penelitian ini adalah: 1) bagaimana perencanaan program boarding school dalam peningkatan prestasi dan karakter religious siswa Ma’hadAl-Qolam MAN 2 Kota Malang,2) bagaimana pelaksanaan program boarding school dalam peningkatan prestasi dan karakter religious siswa Ma’had Al-Qolam MAN 2 Kota Malang,, 3) bagaimana evaluasi program boarding school dalam peningkatan prestasi dan karakter religius siswa Ma’had Al-Qolam MAN 2 Kota Malang, 4) bagaimana hasil program boarding school dalam peningkatan prestasi dan karakter religius siswa Ma’had Al-Qolam MAN 2 Kota Malang, Penelitian ini menggunakan pendekatan kualitatif, dimana dalam hal ini peneliti memahami betul fenomena yang terjadi dan dalam menjaga keaslian data maka peneliti ikut terlibat aktif dan turun kelapangan secara langsung. Hasil penelitian menunjukkan bahwa: 1) perencanaan program dalam peningkatan prestasi dan karakter religious siswa Ma’had Al-Qolam MAN2 Kota Malang menggunakan empat acuan, yaitu: a. Nilai dasar Ma’had, b. visi misi madrasah, b.rencana strategi, c pedoman manajemen; 2) pelaksanaan program peningkatan prestasi diawali dengan a. seleksi penerimaan santri baru, b. Pemetaan kelas santri, c. Program pelaksanaan, d. pola Pembinaan; 3) Evaluasi meliputi a. secara langsung dan b. tidaklangsung. 4) Hasil program yakni a. capaian target dan b.raihan penghargaan.